Avaliação da precisão de aquisição de dados nos Sistemas CAD/CAM: desadaptação marginal horizontal - Lopes, Leonardo Ferreira de Toledo Piza [UNESP] (2015)
Objective: The aim of this study was to evaluate the horizontal marginal fit of frameworks produced by CAD/CAM systems with 3 different data acquisition. Material and Methods: We fabricated 50 frameworks divided into 5 groups, Conventional (Ni- Cr); GI: iTero; GII: CerecBluecam/industrial milling; GIII: 3S; GIV: CerecBluecam/Sirona, all with n = 10. We numbered the specimens and analyzed them randomly. Results: Intra-observer analisys indicated no statistically significant difference (paired t-test=0.019; p=0.985). In relation to the overextended horizontal marginal discrepancy (Positive Values) can analyze that the Control group (Conventional) had significantly (p < 0.001) minor discrepancy values (82 μm) when compared to the CAD / CAM group (144 μm). When comparing the systems intra/extra oral can be appreciated that the intra oral group (Itero) presented statistically best results when comparing(p < 0.001) that the extra oral ( 3s ). Evaluating the difference between the open system with closed was observed that the open system had statistically smaller misfit (p < 0.001). Evaluating the broke of a closed system (Cerec Bluecam) your industrial milling had statistically (p < 0.001) worse adaptation when compared to the laboratorial milling. About the under extended marginal discrepancy, in all analysis there was not found statistically significant difference. Significance: Assessing the horizontal marginal discrepancy was possible to note that in relation to the overextended the control group had statistically better results than the CAD/CAM systems, however the Cerec Bluecam system by sirona milling had better results than all CAD/CAM system and also the control group. There was no difference between the under extended misfit and all analysis